1661b Exploring the combined effect of job strain and occupational physical activity on cardiovascular disease incidence. (24th April 2018) - Ferrario, MM; Veronesi, G; Borchini, R; Roncaioli, M; Grassi, G; Cesana, G
Abstract : Introduction: The aim of the study is to investigate the interplay between job strain (JS) and occupational physical activity (OPA) in determining the risk of major cardiovascular diseases (CVD), in a working male population. Methods: n=1515 participants to three population-based (WHO-MONICA Brianza II and III survey and PAMELA) North Italian cohorts, 25–64 years old, employed and CVD-free at baseline, were available for the analyses. JS was investigated using the Job Content Questionnaire (MONICA-MOPSY short version), and dichotomized as high vs no-high strain. A habitual OPA score was derived from the Baecke Questionnaire (8 items) and categorised in tertiles. Age-adjusted hazard ratios (HRs) and 95% confidence intervals for incidence of CVD (first coronary heart disease or ischaemic stroke, fatal or non-fatal) events were estimated from Cox-proportional hazard models. A sensitivity analysis was carried out stratifying by sport PA levels. Result: In a median 17 years of follow-up, n=102 first CVD events occurred. As compared to the intermediate OPA tertile, workers with low and high OPA showed higher HRs of 1.67 (95% CI: 0.96 to 2.92) and 2.01 (1.17–3.46), respectively. Stratifying by sport PA, the above reported HRs for low and high OPA workers increased to 2.32 (1.15; 4.69) and to 2.54 (1.09; 5.95) when sport PA was below and above the median, respectively. High vs non-high JS workers evidenced an HR of 1.27 (0.76–2.11). When adjusting for age, BMI, alcohol intake, smoking and sport PA, a joint effect was detected between OPA and JS, with the highest HR for workers in the low OPA and high JS category [2.70 (1.17; 6.26)] as compared to workers in the intermediate OPA and non-high JS. Discussion: We observed a joint additive effect between sedentary work and high JS on the incidence of cardiovascular events.